Analysis of the Application of Operational Management in Company Activities PT Aneka Usaha Tanggamus Jaya Unit Usaha Wayku Tanggamus Provinsi Lampung - Ryan Pratama; Defrizal (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to identify how operational management is implemented at PT. Aneka Usaha Tanggamus Jaya Wayku Tanggamus in company activities in the production of bottled drinking water (AMDK). Qualitative descriptive research techniques are used by researchers by analyzing operational management through project management, forecasting management, design of goods and services, managing quality, inventory management, and supply chain management using Miles and Huberman data analysis techniques, namely, data reduction, data display, and concluding drawing, the results found from this research are: In the implementation of operational management PT AUTJ Wayku Tanggamus has implemented project management in the production process and formed company SOPs, in forecasting management PT AUTJ Wayku Tanggamus uses a type of forecasting, namely demand forecasting, in section design gods and services collaborate with external parties in product design and provide services to business partners, partners and customers as outlined in the SOP, Managing Quality which is implemented in quality control is not only carried out alone but in collaboration with local laboratories to carry out quality control PT.AUTJ Wayku Tanggamus established a water reservoir or raw material inventory that is very good and is considered to have very little chance of being contaminated by foreign substances that can damage water quality, and for finished products the company applies.